Smoking behavior and social contexts associated with smoking among dual‐smoker couples. Issue 2 (13th November 2019) - Choi, Seung Hee; Ling, Jiying; Noonan, Devon; Kim, Woojong
Abstract: Objectives: To examine smoking behavior and social contexts related to smoking among dual‐smoker couples. Design: Cross‐sectional online survey study. Sample: A convenience sample of 183 dual‐smoker couples. Measurements: Investigator‐developed survey on smoking and related social contexts. Results: Participants smoked 16.0 cigarettes daily for 14.2 years; 48.4% shared more than half of their smoking time with their spouse. More than half made quit attempts in the past year individually ( M  = 5.3) and jointly ( M  = 2.5). Couples sharing more smoking time were more likely to be motivated to quit ( p  = .002), make quit attempts ( p  < .0001), and be interested in cessation interventions ( p  = .002); but less likely to implement home smoking bans ( p  < .001). Among those who reported quit attempts, 41% quit by themselves and 15.3% sought professional assistance. Most common reasons for relapse were chronic stress and crisis, 63.6%, however, were interested in smoking cessation services, preferably technology‐based interventions. Conclusions: We found smoking interdependence within dual‐smoker couples. Despite high levels of motivation to quit, most did not utilize professional help, leading to low successful quit rates. Technology‐based smoking cessation interventions incorporating spousal support and addressing stress/crisis may best assist dual‐smoker couples.